Fatmawati: Dari Muhammadiyah untuk Negara - Pradita, Silvy Mei (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2021)
Fatmawati: From Muhammadiyah to the Country. This study aims to describe the travel history of a Fatmawati, son of a Muhammadiyah figure in Bengkulu. This study uses the Historical method with four stages, namely data collection (heuristic), source selection (verification), data interpretation (interpretation), and writing history (historiography). The results of this study are Fatmawati is the son of a Muhammadiyah figure in Bengkulu, Fatmawati's childhood almost lost her happiness because of a fight that occurred with her parents due to a married woman who liked her father. But these problems could be overcome because Hassan Din assured Siti Chadijah that he would not remarry. Since she was a teenager, Fatmawati was active in Muhammadiyah through Nasyiatul Aisyiyah (NA), until finally Fatmawati was able to win the heart of a Sukarno and marry her in June 1943. As Sukarno's wife, Fatmawati was indirectly involved and played an important role in Indonesia's independence struggle. One of them was when he sewed the red and white flag which was used as the national flag of the Republic of Indonesia.